2022
DOI: 10.1371/journal.pone.0273299
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaires of interoception do not assess the same construct

Abstract: There are a number of questionnaires assessing the self-reported trait-like aspect of interoception, also called interoceptive sensibility (ISb). Based on the varying purposes of their development and characteristics, however, it is not likely that they assess exactly the same construct. In a community sample of 265 adults, we examined this assumption for three commonly used questionnaires of ISb, namely the Body Awareness subscale of the Body Perception Questionnaire (BPQ-BA), the Body Awareness Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 67 publications
1
11
0
1
Order By: Relevance
“…Together, these findings extend the validity evidence of the MAIA factors as IATs through trait coherence with EC, particularly for the factors that contain regulatory elements. In this way, our findings help clarify this aspect of the construct validity gap on the evaluative constructs of interoception (Vig et al, 2022).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Together, these findings extend the validity evidence of the MAIA factors as IATs through trait coherence with EC, particularly for the factors that contain regulatory elements. In this way, our findings help clarify this aspect of the construct validity gap on the evaluative constructs of interoception (Vig et al, 2022).…”
Section: Discussionsupporting
confidence: 60%
“…Self‐reported indices and beliefs about the tendency to focus on interoceptive stimuli are known as interoceptive sensibility (Baranauskas et al, 2017; Critchley & Garfinkel, 2017; Khalsa et al, 2017; Mehling, 2016), but the construct span is disputed (Desmedt et al, 2022; Todd et al, 2022; Vig et al, 2022). While there are many measurement tools for body awareness, to capture the collection of senses tied to interoceptive processes, Mehling et al (2012) developed a comprehensive scale to elucidate aspects of interoceptive sensibility known as the Multidimensional Assessment of Interoceptive Awareness (MAIA).…”
mentioning
confidence: 99%
“…It is possible that the reported associations (Daubenmier, 2005;Delaney and Anthis, 2010; Tihanyi The questionnaire we used captured more dimensions of the broad construct of interoceptive awareness, thus there was more room for differential results than in case of studies that used questionnaires (typically the BAQ) with a single composite score (Rani and Rao, 1994;Daubenmier, 2005;Impett et al, 2006;Tihanyi et al, 2016b). It may not even be reasonable to draw a parallel between the aforementioned instruments, as Vig et al (2022) recently found that correlations between the BAQ and the MAIA scales Not Worrying and Not Distracting are virtually non-existent, as well as only weak to moderate associations have been found with the remaining six subscales. Consequently, the authors suggest that these instruments cannot be used interchangeably, as they presumably do not measure the same underlying construct.…”
Section: Discussionmentioning
confidence: 99%
“…Interoceptive attention was measured using the Multidimensional Assessment of Interoceptive Awareness (MAIA; Mehling et al, 2012 ). The MAIA, a gold standard measure of interoceptive sensibility ( Desmedt et al, 2022 ; Vig, Koteles & Ferentzi, 2022 ), contains 32 items inquiring about experiences of interoceptive attention and awareness across eight subscales: Noticing, Attention Regulation, Emotional Awareness, Self-Regulation, Body Listening, and Trusting subscales, Not Worrying, and Not Distracting. Items are measured on a Likert-type scale ranging from 0 ( never ) to 5 ( always ).…”
Section: Methodsmentioning
confidence: 99%
“…All inventories putatively measure the lived experience of interoception, yet the most common interoception-related questionnaires have been found to index discreet dimensions ( Desmedt et al, 2022 ; Vig, Koteles & Ferentzi, 2022 ). Most available questionnaires focus on attention and emotional reactions to bodily sensations ( e.g.…”
Section: Introductionmentioning
confidence: 99%